2014
DOI: 10.1182/blood-2013-08-520882
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of thrombotic properties of persistent autoimmune anti-β2GPI antibodies in the mouse model of antiphospholipid syndrome

Abstract: • A1-A1 inhibits thrombotic properties of anti-b2GPI antibodies in mice.• A1-A1 does not affect thrombus size in the absence of anti-b2GPI antibodies.Antiphospholipid syndrome (APS) is an autoimmune disorder with increased risk for thrombosis and pregnancy losses. b2-glycoprotein I (b2GPI) is the major antigen for clinically relevant antibodies in APS. We engineered a molecule, A1-A1, which interferes with 2 prothrombotic mechanisms in APS: the binding of b2GPI to negatively charged cellular surfaces and ApoE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 56 publications
1
32
0
Order By: Relevance
“…A1–A1 not only interferes with the binding of β2GPI/antibody complexes to ApoER2, but also prevents their association with anionic phospholipids, therefore inhibiting two potentially harmful activities of β2GPI/antibody complexes . Most importantly, we demonstrated that infusion of A1–A1 in mice abrogated the increase in thrombus size caused by the presence of β2GPI/antibody complexes .…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…A1–A1 not only interferes with the binding of β2GPI/antibody complexes to ApoER2, but also prevents their association with anionic phospholipids, therefore inhibiting two potentially harmful activities of β2GPI/antibody complexes . Most importantly, we demonstrated that infusion of A1–A1 in mice abrogated the increase in thrombus size caused by the presence of β2GPI/antibody complexes .…”
Section: Introductionmentioning
confidence: 68%
“…β2GPI/antibody complexes are prothrombotic in APS patients and in mice . Disruption of a protective shield formed by annexin V on anionic phospholipids by β2GPI/antibody complexes is one of the thrombogenic mechanisms in APS .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of the anti-b2GP1 antibody/b2GP1 complex to cell receptors 19,36,[39][40][41] has been studied, and receptors have been proposed to be involved in thrombus enhancement. The inhibition of enhancement of thrombus formation in the absence of specific receptors [20][21][22]42 or in the presence of inhibitors of receptors 43 suggest that some receptors may not be directly involved in the pathway initiated by the anti-b2GP1 autoantibody/b2GP1 complex. Therefore, we visualized both cell binding and cell activation induced by the anti-b2GP1 autoantibody/b2GP1 complex in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that A1‐A1 preferentially binds to β2GPI when it is dimerized by anti‐β2GPI antibody, compared with β2GPI alone . A1‐A1 inhibited the anti‐β2GPI‐dependent increase of thrombus size in laser‐induced thrombosis in BALB/c mice infused with anti‐β2GPI antibodies isolated from a patient with APS and in (NZWxBXSB)F1 male mice with spontaneous anti‐β2GPI antibodies .…”
Section: Introductionmentioning
confidence: 93%